A table of Balmer γ line shapes for the diagnostic of magnetic fusion plasmas. (November 2015) - Rosato, J.; Bufferand, H.; Koubiti, M.; Marandet, Y.; Stamm, R.
Abstract: Spectral profiles of the D γ line have been calculated in magnetic fusion plasma conditions for diagnostic purposes. This paper reports on the elaboration of a table devoted to spectroscopic applications in tokamak divertors. An overview of the method, together with the physics underlying the broadening of spectral lines, is given. A special emphasis is put on the role of the simultaneous action of the Stark and Zeeman effects. Abstract : Highlights: We present new calculations of Stark–Zeeman line shapes for magnetic fusion plasma diagnostics. The sensitivity of spectra to the electron density is examined. Applications to synthetic diagnostics in a virtual plasma background are discussed.